Enhancing Speaking Skills of Senior High School Students Using Sims Freeplay - Oktari, Eskananti Intan; Basikin, Basikin; Umar, Nasir (International Journal of Contemporary Studies in Education, 2025)
This study aimed to improve students’ speaking skills using Sims Freeplay through action research based on the Kemmis and McTaggart model, which includes five steps: reconnaissance, planning, action, observation, and reflection. The participants were 29 students from class XI-1 of a senior high school in Yogyakarta, consisting of 12 females and 17 males. Qualitative data were collected through observations and interviews, while quantitative data were gathered using pre-tests and post-tests. Data analysis involved five steps: assembling, coding, comparing, interpreting, and reporting the outcomes. The validity of the data was measured using democratic, outcomes, process, catalytic, and dialogic validity, while reliability was ensured through time triangulation. The results showed improvements in students’ speaking skills, with mean scores increasing from the pre-test (12.28) to post-test cycle I (13.28) and post-test cycle II (14.31), reflecting an 8% increase in cycle I and 9% in cycle II. Reflection from cycle I revealed improvements in vocabulary, fluency, pronunciation, grammar, and sentence organization. Anxiety levels decreased from a mean score of 14.87 to 12.66, while motivation increased from 17.21 to 20.20. Sims Freeplay proved to be an effective and engaging tool for learning English, significantly enhancing students’ speaking skills and creating a positive learning experience.